2020
DOI: 10.3892/or.2020.7532
|View full text |Cite
|
Sign up to set email alerts
|

Filamin B extensively regulates transcription and alternative splicing, and is associated with apoptosis in HeLa cells

Abstract: Post-transcriptional mechanisms are an important approach in the treatment of cancer, and may also be hijacked by tumor cells to help adapt to the local microenvironment. Filamin B (FLNB), an actin-binding protein that provides crucial scaffolds for cell motility and signaling, has also been identified as an RNA-binding protein. Recent studies demonstrated that FLNB might play an important role, not only in skeletal development, but also in regulating tumorigenesis; however, the effects of dysregulated express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Two lysosomal proteins (legumain and acid phosphatase 2, lysosomal) were likewise lower in abundance in BL25. Filamin B is an actin-binding cytoskeletal protein, but also binds RNA and decreased transcript levels of filamin B have resulted in downregulation of apoptosis and genes that function in immunity and inflammation (76), which is consistent with some of the functions discussed above. Besides the common proteins involved in lipid metabolism that were significantly lower in abundance in both populations as mentioned above (sterol carrier protein 2a, phytanoyl-CoA 2-hydroxylase, fatty acid synthase), an additional lipid metabolism protein (lipase) was significantly reduced in the BL population.…”
Section: Chronic Warm Acclimation Increases Chromatin Regulation and Transcriptional Control While Reducing Translation And Fatty Acid Mesupporting
confidence: 79%
“…Two lysosomal proteins (legumain and acid phosphatase 2, lysosomal) were likewise lower in abundance in BL25. Filamin B is an actin-binding cytoskeletal protein, but also binds RNA and decreased transcript levels of filamin B have resulted in downregulation of apoptosis and genes that function in immunity and inflammation (76), which is consistent with some of the functions discussed above. Besides the common proteins involved in lipid metabolism that were significantly lower in abundance in both populations as mentioned above (sterol carrier protein 2a, phytanoyl-CoA 2-hydroxylase, fatty acid synthase), an additional lipid metabolism protein (lipase) was significantly reduced in the BL population.…”
Section: Chronic Warm Acclimation Increases Chromatin Regulation and Transcriptional Control While Reducing Translation And Fatty Acid Mesupporting
confidence: 79%
“…41 Dysregulated splicing of Fln B was also found to regulate tumor cell plasticity. 42 Our results from this study revealed that Fln B was significantly decreased with increasing age, accompanied by an increase in Fln A and active integrin β1 in older WKY VSMCs, which were not reversed by CCG. Together with the previous results, it is reasonable to postulate that disruption of Fln B to A balance may target upstream mediators of Rho/SRF signaling, regulating VSMC plasticity in an SRF-aSMA–independent manner, which may explain the ineffectiveness of CCG in counteracting aging-related aortic stiffness.…”
Section: Discussionmentioning
confidence: 44%
“…The filamin b gene ( flnb ) encodes an actin-binding protein that can cross-link actin filaments and link actin filaments to membrane-bound proteins ( Nakamura et al, 2011 ). In addition to its actin-binding functions, FlnB has also been demonstrated to play a role in alternative splicing of apoptosis-related transcripts in HeLa cell death ( Ma et al, 2020 ), and pro-apoptotic effects as a part of the type I interferon signaling pathway as assayed in mammalian cells ( Jeon et al, 2008 ; Whitmarsh, 2009 ). Tubulin polyglutamylase TTLL5 (TTLL5) is a microtubule associated protein that glutamylates alpha tubulin subunits.…”
Section: Discussionmentioning
confidence: 99%